2020
DOI: 10.1080/07391102.2020.1834457
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the inhibition of SARS-CoV2 main protease by Indian medicinal plant-derived antiviral compounds

Abstract: A novel coronavirus (SARS-CoV2) has caused a major outbreak in humans around the globe, and it became a severe threat to human healthcare than all other infectious diseases. Researchers were urged to discover and test various approaches to control and prevent such a deadly disease. Considering the emergency and necessity, we screened reported antiviral compounds present in the traditional Indian medicinal plants for the inhibition of SARS-CoV2 main protease. In this study, we used molecular docking to screen 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…To the best of our knowledge, there are no other MD simulations of paritaprevir–RBD and amentoflavone–RBD complexes. But, there are many stable MD simulations of the amentoflavone complex with the main protease (Ghosh et al, 2020 ; Lokhande et al, 2020 ; Mishra et al, 2020 ; Patil et al, 2021 ; Saravanan et al, 2020 ; Swargiary et al, 2020 ). For paritaprevir and simeprevir, stable MD simulations with the main protease and the uridylate-specific endoribonuclease (NSP15) have been obtained (Alamri et al, 2020 ; Khan, Jha, Amera, et al, 2020 ; Khan, Jha, Singh, et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there are no other MD simulations of paritaprevir–RBD and amentoflavone–RBD complexes. But, there are many stable MD simulations of the amentoflavone complex with the main protease (Ghosh et al, 2020 ; Lokhande et al, 2020 ; Mishra et al, 2020 ; Patil et al, 2021 ; Saravanan et al, 2020 ; Swargiary et al, 2020 ). For paritaprevir and simeprevir, stable MD simulations with the main protease and the uridylate-specific endoribonuclease (NSP15) have been obtained (Alamri et al, 2020 ; Khan, Jha, Amera, et al, 2020 ; Khan, Jha, Singh, et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, amentoflavone is an effective inhibitor (IC 50 ¼ 8.3 mM) of the SARS-CoV main protease (Ryu et al, 2010). In the recent in silico studies (Ghosh et al, 2020;Lokhande et al, 2020;Mishra et al, 2020;Patil et al, 2021;Peterson, 2020;Puttaswamy et al, 2020;Saravanan et al, 2020;Swargiary et al, 2020), amentoflavone has been reported to bind tightly to the main protease of SARS-CoV-2. There are also three docking studies targeting spike glycoprotein of SARS-CoV-2, in which amentoflavone was found among the hit compounds with the binding energies: À7.6 kcal/mol (Wei et al, 2020), À8.7 kcal/mol (Puttaswamy et al, 2020), and À10.2 kcal/mol (Rameshkumar et al, 2021).…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, free energy calculations on these compounds performed by using the molecular docking procedure. The results suggested that amentaflavone, hypericin, and Torvoside H respectively complexed with SARS-CoV-2 Mpro show better binding with stabilizing interactions and provided valuable information in developing new, novel and natural anti-viral drugs for COVID-19 [9]. In addition, taraxerol isolated from Clerodendrum species has shown potential antiviral activities with desirable pharmacological features [12].…”
Section: Ayurvedamentioning
confidence: 96%
“…It has been shown that Coptidis rhizome, Meliae cortex, Sanguisorbae radix, Cimicifuga rhizome, and Phellodendron cortex exhibit anti-coronavirus activity. Sophorae radix, Tor ilis fructus, and Acanthopanacis cortex decreased intracellular viral RNA levels with corresponding viral protein decreases [9]. The antiviral activity of some phytoconstituents present in traditional medicinal plants from Ayurveda were also investigated against spike glycoprotein of SARS-COV-2 as well as its host ACE-2 receptor.…”
Section: Ayurvedamentioning
confidence: 99%